2009
DOI: 10.2353/jmoldx.2009.080125
|View full text |Cite
|
Sign up to set email alerts
|

CpG Methylation Analysis—Current Status of Clinical Assays and Potential Applications in Molecular Diagnostics

Abstract: Methylation of CpG islands in gene promoter

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 139 publications
0
15
0
5
Order By: Relevance
“…17,32,[37][38][39][40][41][42][43][44][45] Genome-wide DNA hypomethylation plays an important role in genomic instability by reactivating transposable DNA sequences and, therefore, contributes to colorectal carcinogenesis. 1,3-6,35,39,46 -48 Previous studies have reported that most carcinomas of colon, stomach, breast, lung, prostate, liver, and esophagus show hypomethylation of LINE-1 compared with matched normal tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,32,[37][38][39][40][41][42][43][44][45] Genome-wide DNA hypomethylation plays an important role in genomic instability by reactivating transposable DNA sequences and, therefore, contributes to colorectal carcinogenesis. 1,3-6,35,39,46 -48 Previous studies have reported that most carcinomas of colon, stomach, breast, lung, prostate, liver, and esophagus show hypomethylation of LINE-1 compared with matched normal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Assays to measure DNA methylation, which are important in epigenetic research and clinical diagnostics, 17 typically rely on conversion of unmethylated cytosine to uracil by sodium bisulfite. However, no previous study has evaluated the precision of bisulfite conversion to measure LINE-1 methylation.…”
mentioning
confidence: 99%
“…6,9,10 CpG methylation is a central mechanism of epigenetic gene regulation, and occurs early in gastric cancer development, affecting genes known to have roles in gastric carcinogenesis such as MLH1, CDKN2A (p16), CDH1 (E-cadherin), RUNX3, COX-2, MGMT, and others. [11][12][13][14][15][16][17][18] Altered CpG methylation is already detected in mucosa with gastritis, is associated with chronic inflammation in response to H. pylori infection, and has been shown to be partially reversible after eradication of H. pylori infection. [19][20][21] In our study we used next-generation sequencing of bisulfite-treated DNA, which allows for sensitive quantification of the level of methylation at each individual CpG site present on the sequenced region.…”
mentioning
confidence: 99%
“…The first generation sequencing used to characterize the glioblastoma landscape captures the most prevalent mutations. They did not analyze the deeper heterogeneity of low prevalence mutations that have been found in several tumor types, including colon cancer [129]. Efforts to examine whether such sub-clonal diversity exist in glioblastoms using highly sensitive techniques [130] have not identified the presence of low-prevalence mutations.…”
Section: Mutationsmentioning
confidence: 99%